Impact of Diabetes Mellitus on Percutaneous Coronary Intervention in Chinese Patients: A Large Single-Center Data. (July 2018) - Wang, Huanhuan; Gao, Zhan; Song, Ying; Tang, Xiaofang; Xu, Jingjing; Jiang, Ping; Jiang, Lin; Chen, Jue; Gao, Lijian; Song, Lei; Zhang, Yin; Zhao, Xueyan; et al.
Aim: To investigate the impact of diabetic status on 2-year clinical outcomes in Chinese patients undergoing contemporary percutaneous coronary intervention (PCI) treatment. Methods and Results: A total of 10 724 consecutive patients underwent PCI at Fu Wai Hospital were prospectively collected. Two-year clinical outcomes were compared between patients with and without diabetes mellitus (DM). Diabetic patients had more baseline clinical risks and more extensive coronary disease. During 2-year follow-up, the rates of all-cause death, myocardial infarction (MI), revascularization, and major adverse cardiac events (MACE) were significantly higher in DM group. After multivariable-adjusted Cox regression analysis, DM was an independent risk factor for MACE but not for the individual components of MACE. After performing propensity score matching, rates of all-cause death, MI, revascularization, stroke, stent thrombosis, and MACE were not significantly different between the 2 groups, and DM was not predictive of MACE and any clinical adverse outcomes. Conclusions: Diabetic patients who underwent PCI had worse prognosis including death and repeat revascularization during 2-year follow-up, but DM was not an independent risk factor for adverse clinical outcomes.